Association of diabetes mellitus with thyroid cancer risk: A meta-analysis of cohort studies. Issue 47 (November 2017) - Li, Hongtao; Qian, Jun
Abstract: Background: Diabetes mellitus (DM) is inconsistently associated with thyroid cancer risk. The purpose of this study was to summarize findings from cohort studies regarding the strength of the association of DM with subsequent thyroid cancer risk. Methods: Electronic searches were performed in PubMed, EmBase, and the Cochrane Library to identify studies from inception to July 2016. Cohort studies reporting risk estimates with 95% confidence intervals (CIs) of thyroid cancer in DM and non-DM patients were included. A random-effects meta-analysis was performed to the risk of thyroid cancer in DM compared with non-DM participants. Results: Sixteen cohort studies were included, with a total of 10, 725, 884 individuals. These studies reported a total of 8032 cases of thyroid cancer. Overall, DM was associated with an increased risk of thyroid cancer (relative risk [RR], 1.20; 95% CI, 1.09–1.33; P < .001). Further, there was no significant difference was found between DM and non-DM for the risk of thyroid cancer in men (RR, 1.14; 95% CI, 1.00–1.30; P = .057), while a significant correlation was found in a pooled analysis in women (RR, 1.11; 95% CI, 1.06–1.17; P < .001). Finally, subgroup analyses suggested that country and mean age might correlate with the relationship between DM and the risk of thyroid cancer. Conclusion: This study suggested that patients with DM have significantly increased risk of thyroid cancer compared nondiabetics. This positive association was prominent in women, and not significant in men. Further large-scale studies are required to verify the nature of the association, which should be evaluated in specific subpopulations.